Pengaruh Teknik Akupresur pada Titik LI4 terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif pada Ibu Bersalin di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Defmiyanti Defmiyanti; Anisya Selvia; Nelli Roza (Lembaga Pengembangan Kinerja Dosen, 2026)
Labor pain is a physiological condition commonly experienced by mothers giving birth, especially during the first active phase, which often causes anxiety and tension. One non-pharmacological method that can be used to reduce pain is the acupressure technique, especially at the LI4 point, which is known to have an analgesic effect. This study aims to determine the effect of acupressure techniques at the LI4 point on reducing labor pain in the first active phase of labor in mothers giving birth in the Sei Health Center working area. Slender. This research is quasi-experimental with a nonequivalent control group design. The respondents for this research were 16 mothers in labor who met the inclusion criteria. The sampling technique used was nonprobability sampling, which was chosen as purposive sampling. Based on the research results, it was found that the labor pain of women giving birth at the Hanika Clinic and the AMC Clinic after acupressure was carried out at point LI4, some women in labor experienced moderate pain (68.8%) and a small number experienced mild pain (31.3%). The results of statistical tests show that there is an influence of the acupressure technique at point LI4 on reducing labor pain during the first active phase in mothers giving birth (p value < α (<.001)). The results showed that administering acupressure at the LI4 point significantly reduced the level of labor pain, compared to before the intervention. Thus, this technique can be used as an alternative pain management that is effective, safe and easy to do during the birthing process